2017
DOI: 10.1038/s41598-017-09551-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel Meju starter culture using plant extracts with reduced Bacillus cereus counts and enhanced functional properties

Abstract: We developed a novel type of Meju starter culture using single and combined extracts of Allium sativum (garlic clove), Nelumbo nucifera (lotus leaves), and Ginkgo biloba (ginkgo leaves) to improve the quality and functionality of Meju-based fermented products. Meju samples fermented with plant extracts (10 mg/ml) showed phenolic contents of 11.4–31.6 mg/g (gallic acid equivalents). Samples of extracts (garlic clove, lotus leaves, ginkgo leaves and their combination) fermented with Meju strongly inhibited tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…The moderately acidic pH in the Doenjang samples attests it safe for consume, contrary to the excessively low pH which adversely affects health by causing acidosis. The results are consistent with previous findings, signifying the role of starter culture and alterations in processing conditions and ingredients on the pH of prepared Doenjang 6,15 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The moderately acidic pH in the Doenjang samples attests it safe for consume, contrary to the excessively low pH which adversely affects health by causing acidosis. The results are consistent with previous findings, signifying the role of starter culture and alterations in processing conditions and ingredients on the pH of prepared Doenjang 6,15 .…”
Section: Resultssupporting
confidence: 92%
“…Results are assisted with the number of reports presenting the diverse amount of phenolics and flavonoids in the soy fermented food 24,25 . In a recent study, variations in phenolic and flavonoid contents were reported in Doenjang formed by the addition of different plant materials 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the anti-bacterial, anti-oxidant, and anti-obesity effects of lotus and its extracts have been known for many years [24,52], little is known about the activity of LAE on cancer cell migration. We demonstrated that LAE had the potential inhibitory activity for cell migration and EMT in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…All the collected ltrate was concentrated to dryness by evaporation on a rotary evaporator, and then dissolved in DMSO and ltered by a membrane lter with 0.22μm pore size (Millipore, USA). Finally, LAE was diluted into several concentrations (10,25,50, 100, 250µg/ml) for cell treatments and stored at 4 o C.…”
Section: Lae Treamentmentioning
confidence: 99%